Comparison of Maternal Bleeding During Preterm and Term Cesarean Delivery - Saima Irfan; Rubina Mushtaq; Sumaira Khan; Maliha Khawar; Nafeesa Hiba (Pakistan Armed Forces Medical Journal, 2024)
Objective: To compare maternal bleeding in pregnant women undergoing term and pre-term Cesarean delivery.